Depression Among the Elderly: A Cross Sectional Study in A Rural Community of South India - Poonam Ramesh Naik; Abhay Subhashrao Nirgude (Medsci Publications, 2015)
Introduction: Depression among the elderly often remains unde- tected and thereby untreated. Depression results in cognitive im- pairment and compromises their quality of life. Objective of the study was to determine the magnitude of depression among the elderly and study the factors associated with it. Methodology: A cross sectional study was conducted among 230 elderly. Data was collected by house to house visit to elicit infor- mation on socio demographic profile. Geriatric depression scale (GDS-30) was used to assess the burden of depression. Results: The mean age of the study participants was 66.33 years. Almost 59.6% were depressed, 79.5% had mild depression and 20.4% had severe depression. Depression was more among the fe- males, unemployed and those belonging to class V socio - eco- nomic status. Conclusion: High magnitude of depression was observed among the elderly. Identification of the risk groups will thus facilitate for- mulation of health care services for early identification of depres- sion and management.